GENDER RELATIONS PORTRAYED IN NGADA LEGEND “PENU AND VEGU THE ORPHAN” - Duka, Yofita L (Fakultas Hukum dan Sosial Humaniora Universitas Flores, 2025)
This paper looks at gender relations in “Penu and Vegu the Orphan”, one of the legends from Ngada. The thematic analysis of this paper revealed that the legend portrays three intertwined gender relations, such as (i) patriarchal authority, (ii) female agency and self-transformation, and (iii) gendered labor and domestic power. The analysis demonstrates that simplistic binary notions of male dominance or female subordination are challenged through Penu’s character. This female protagonist navigated a male-dominated society, using her agency through nature-driven transformation and domestic works. This paper contributes to a wider discussion of gender in folklore by underscoring the importance of indigenous oral literature as a medium for understanding the diversity of gender constructions beyond Western contexts.